Perceived restorativeness of children's school playground environments: Nature, playground features and play period experiences. (March 2015) - Bagot, Kathleen L.; Allen, Felicity Catherine Louise; Toukhsati, Samia
Abstract: With little research examining children's restorative environments, the design of environments supportive of children's functioning is limited. The aim of this study was to examine the predictors of perceived restorativeness of children's school playgrounds, using Attention Restoration Theory. Children ( N  = 550, 46% boys, M age  = 9.73 years, SD  = 1.21) from 14 schools reported playground perceived restorativeness and play period experiences (affect, physical activity, social activity, perceived affordances). Playground characteristics of nature, size, play areas, play equipment and ratio of total grounds were assessed. After controlling for gender, age and playground size, vegetation volume was the only significant naturalness measure predicting perceived restorativeness. Play period experiences explained more variance than physical characteristics. With only moderate levels of perceived restorativeness revealed, the potential for school grounds to enhance children's functioning remains. Factors contributing to children's restorative environments may differ from adults, requiring children's inclusion in the research and design of their environments. Highlights: Moderate levels of perceived restorativeness reveal potential for enhancing playground design. Vegetation volume was the only physical predictor of perceived restorativeness, albeit a weak one. Play period experiences contributed more than nature to perceived restorativeness of grounds. Smaller, greener playgrounds may yield strongest benefits.